2011
DOI: 10.3138/ptc.2010-07
|View full text |Cite
|
Sign up to set email alerts
|

“They put you on your toes”: Physical Therapists' Perceived Benefits from and Barriers to Supervising Students in the Clinical Setting

Abstract: Despite different disciplines and models of supervision, there is considerable synchronicity in the issues reported by physical therapists and other disciplines. Embedding the value of clinical teaching in the institution, along with strong communication links among academic partners, institutions, and potential clinical faculty, may mitigate barriers and increase the commitment and satisfaction of teaching staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
53
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 26 publications
5
53
0
Order By: Relevance
“…4 Reported barriers include managing time constraints and coping with challenging students. 5 Although early physiotherapy research identified that student clinical placements within healthcare services enhance overall productivity, 6 quantitative data identifying student contribution to service delivery are limited. These data would be valuable to inform health policy, planning and resourcing requirements of clinical placements, as well as enhancing capacity and skill to provide quality clinical education.…”
Section: Introductionmentioning
confidence: 99%
“…4 Reported barriers include managing time constraints and coping with challenging students. 5 Although early physiotherapy research identified that student clinical placements within healthcare services enhance overall productivity, 6 quantitative data identifying student contribution to service delivery are limited. These data would be valuable to inform health policy, planning and resourcing requirements of clinical placements, as well as enhancing capacity and skill to provide quality clinical education.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, patients became involved in the students' education and subsequently increased their own knowledge. 39 Future research should investigate the influence of athletic training students on patient outcomes.…”
Section: Benefits Of Being a Preceptormentioning
confidence: 99%
“…3 The fear of having a difficult or struggling student can be a deterrent to therapists who might otherwise offer to supervise a student. 4 Although there is no denying that a struggling student can demand more of a therapist's time and skills, can we be proactive to relieve this burden and perhaps lessen the fear? Are there ways to communicate this support to a potential clinical instructor that would help abate or lessen fears (and stress) before he or she makes the decision to offer an internship?…”
mentioning
confidence: 99%